2016
DOI: 10.3390/rs8050404
|View full text |Cite
|
Sign up to set email alerts
|

Using NDVI and EVI to Map Spatiotemporal Variation in the Biomass and Quality of Forage for Migratory Elk in the Greater Yellowstone Ecosystem

Abstract: Abstract:The Normalized Difference Vegetation Index (NDVI) and the Enhanced Vegetation Index (EVI) have gained considerable attention in ecological research and management as proxies for landscape-scale vegetation quantity and quality. In the Greater Yellowstone Ecosystem (GYE), these indices are especially important for mapping spatiotemporal variation in the forage available to migratory elk (Cervus elaphus). Here, we examined how the accuracy of using MODIS-derived NDVI and EVI as proxies for forage biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 70 publications
3
82
0
2
Order By: Relevance
“…3. Although linear models of summer forage-NDVI relationships performed poorly, we found that NDVI variables (NDVI and DaysToMax) could be used in a broader modeling effort to depict spatiotemporal variation in biomass, N, DN, and DE by incorporating nonlinear forage-NDVI relationships (Kawamura et al 2005, Santin-Janin et al 2009, Garroutte et al 2016) and other covariates known to influence forage characteristics (i.e., Veg, Coast). Notes: Forage conditions were assessed relative to the Normalized Difference Vegetation Index (NDVI), the difference in the number of days between the sampling date and the annual maximum NDVI value (DaysToMax), distance to the coast (Coast; calculated per 10 km), and vegetation type (reference class = tussock tundra).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…3. Although linear models of summer forage-NDVI relationships performed poorly, we found that NDVI variables (NDVI and DaysToMax) could be used in a broader modeling effort to depict spatiotemporal variation in biomass, N, DN, and DE by incorporating nonlinear forage-NDVI relationships (Kawamura et al 2005, Santin-Janin et al 2009, Garroutte et al 2016) and other covariates known to influence forage characteristics (i.e., Veg, Coast). Notes: Forage conditions were assessed relative to the Normalized Difference Vegetation Index (NDVI), the difference in the number of days between the sampling date and the annual maximum NDVI value (DaysToMax), distance to the coast (Coast; calculated per 10 km), and vegetation type (reference class = tussock tundra).…”
Section: Discussionmentioning
confidence: 96%
“…In addition to NDVI, we included the variable DaysToMax to account for temporally varying forage-NDVI relationships (Santin-Janin et al 2009, Garroutte et al 2016. To meet this objective, we modeled variation in field measurements of forage biomass, N, DN, and DE across the growing season as a function of NDVI variables and base habitat covariates.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Remotely sensed vegetation indices are well established tools of wildlife research and management that can serve as proxies for landscape level changes in biomass and nutrient quality without the repeated destructive sampling of vegetation [12][13][14][15][16]. Of these indices, the Normalized Difference Vegetation Index (NDVI) is one of easiest to calculate, most commonly available and has been proven to be an effective tool for monitoring vegetative changes across a wide range of terrestrial ecosystems, including alpine and arctic tundra, grasslands, and temperate and tropical forests [14][15][16][17][18][19][20], see [21] for a review. The index is a simple ratio calculation of the red and near-infrared (NIR) reflectance bands that is sensitive to the reflected photosynthetically active radiation of plants [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [21] also address grassland productivity in a Southern Alberta prairie using airborne imaging spectrometry combined with ground sampling and eddy covariance data, showing greater productivity in sites with higher biodiversity based on species richness and the Shannon Index. Garroutte and Hansen [22] evaluated the quality of grasslands for elk habitat in the Yellowstone River Basin using seasonal MODIS EVI and NDVI. Zhao et al [23] address the optimal detection of biochemical indicators for species mapping, and two papers show the potential of mapping foliar traits related to ecosystem functionality.…”
mentioning
confidence: 99%